Makna Simbolik Upacara Coka Iba Bagi Masyarakat Weda Di Kabupaten Halmahera Tengah - Karim, Rahman A (JURNAL ILMIAH SOCIETY, 2015)
Traditional ceremony in public life has a purpose to establish the relationship between human beings , between man and nature and between man and God . CokaIba is a traditional ceremony performed by people in these three areas in the district Halmahera Tengah are Patani, Weda and Maba. This is ceremony held on eachcommemorate the great day of Islam is Prophet Muhammad 'sMaulid. This study used qualitative methods. Data obtained by the observation and deep interview. The research aims to describe the process of the ceremony, analyzingmeaning of symbols and changes in the CokaIba ceremony. The research carried in Weda district Halmahera Tengah by focusing on the implementation process of the ceremony and symbolic meaning of CokaIba ceremony for Weda society. The research, researchers conducted observations, documentation and interviews with key informants know about the object of research .IbaCokaceremonywasconductedbyWeda societyuntil now. Valuesandmeanings embodiedin the process CokaIba ceremony the pack incustom (Fagogoru) whichare characteristic ofWedasocietythathas prevailedin the society, and made reference tobehavedailyWedasociety. Keywords : Meaning, Symbolic, CokaIba Ceremony.